Determination of the activation energy of A-center in the uniaxially deformed n-Ge single crystals - S. V. Luniov; A. I. Zimych; P. F. Nazarchuk; S. A. Moroz; L. N. Polishchuk; V. T. Maslyuk; I. G. Megela (Âderna Fìzika ta Energetika, 2017)
Based on the decisions of electroneutrality equation and experimental results of measurements of the piezo-Hall-effect the dependences of activation energy of the deep level A-center depending on the uniaxial pressure along the crystallographic directions [100], [110] and [111] for n-Ge single crystals, irradiated by the electrons with energy 10 MeV are obtained. Using the method of least squares approximational polynomials for the calculation of these dependences are obtained. It is shown that the activation energy of A-center deep level decreases linearly for the entire range of uniaxial pressure along the crystallographic direction [100]. For the cases of uniaxial deformation along the crystallographic directions [110] and [111] decrease of the activation energy according to the linear law is observed only at high uniaxial pressures, when the A-center deep level interacts with the minima of the germanium conduction band, which proved the lower at the deformation. The various dependences of the activation energy of A-center depending on the orientation of the axis of deformation may be connected with features of its microstructure.